EFFECTS OF SEAWATER CARBONATE ION CONCENTRATION AND TEMPERATURE ON SHELL U, MG, AND SR IN CULTURED PLANKTONIC FORAMINIFERA - Russell A.D.; Spero H.J.; Hönisch B.; Lea D.W. (My University, 2004)
We investigate the sensitivity of U/Ca, Mg/Ca, and Sr/Ca to changes in seawater [CO32−] and temperature in calcite produced by the two planktonic foraminifera species, Orbulina universa and Globigerina bulloides, in laboratory culture experiments. Our results demonstrate that at constant temperature, U/Ca in O. universa decreases by 25 ± 7% per 100 μmol [CO32−] kg−1, as seawater [CO32−] increases from 110 to 470 μmol kg−1. Results from G. bulloides suggest a similar relationship, but U/Ca is consistently offset by ∼+40% at the same environmental [CO32−]. In O. universa, U/Ca is insensitive to temperature between 15°C and 25°C. Applying the O. universa relationship to three U/Ca records from a related species, Globigerinoides sacculifer, we estimate that Caribbean and tropical Atlantic [CO32−] was 110 ± 70 μmol kg−1 and 80 ± 40 μmol kg−1 higher, respectively, during the last glacial period relative to the Holocene. This result is consistent with estimates of the glacial–interglacial change in surface water [CO32−] based on both modeling and on boron isotope pH estimates. In settings where the addition of U by diagenetic processes is not a factor, down-core records of foraminiferal U/Ca have potential to provide information about changes in the ocean’s carbonate concentration.Below ambient pH (pH < 8.2), Mg/Ca decreased by 7 ± 5% (O. universa) to 16 ± 6% (G. bulloides) per 0.1 unit increase in pH. Above ambient pH, the change in Mg/Ca was not significant for either species. This result suggests that Mg/Ca-based paleotemperature estimates for the Quaternary, during which surface-ocean pH has been at or above modern levels, have not been biased by variations in surface-water pH. Sr/Ca increased linearly by 1.6 ± 0.4% per 0.1 unit increase in pH. Shell Mg/Ca increased exponentially with temperature in O. universa, where Mg/Ca = 0.85 exp (0.096*T), whereas the change in Sr/Ca with temperature was within the reproducibility of replicate measurements.